PENDIDIKAN MULTIKULTURAL SEBAGAI ALTERNATIF PENANAMAN NILAI MORAL DALAM KEBERAGAMAN - Kusmaryani, Rosita Endang (Paradigma, 2015)
One of the relevant issues to current condition is the diversity in society. This is the result of mobility and information stream which develops more and more rapidly. Foreign cultural values flow into the society, following the stream and give positive as well as negative impacts. This condition of diversity is often assumed as a threat for the unity of nation and state. Oftentimes, certain rules and regulations made as the responds to the diversity turn out to be a facility for the majority culture to dominate. The slogan of "Bhinneka Tunggal Ika" (unity in diversity) as an inheritance of the New Order era constitutes the case which shows how multi-cultures was incorrectly managed by disregarding multiculturalism itself. An assumption that diversity will endanger the wholeness of our nation becomes the reason to force the diversity be kept in an integrity and unity, which eventually leads to the existence of monoculturalism. Domination of the majority culture, the legacy from incorrect perception and management of Bhinneka Tunggal Ika in the past gives impact to various aspects of life in the present Indonesian society. The lack of comprehensive understanding for multiculturalism even causes moral decadence of the young generation. Such merits as togetherness, appreciation and respect to others, and mutual cooperation are vanishing. The arrogance due to domination of majority culture causes lack of understanding in interactions with other cultures or other people. This condition turns to become a challenge for education milieu to give more orientation to multicultural understanding. Schools, through the teaching-learning process, need to emphasize that diversity is a potential wealth and worth understanding, and should not be considered a negative aspect. Multicultural education is expected to be the solution for the problems of national moral degradation. Key words: diversity, multiculturalism, majority culture